Human Resource Management Practices And Institutional Challenges In Ethiopian Secondary Schools - Asnakew Legesse Engdia (Universitas Pakuan, 2025)
Human resource management (HRM) plays a strategic role in improving organizational effectiveness, particularly in educational institutions where teachers represent the core driver of instructional quality and school performance. Despite growing policy attention toward educational reform in Ethiopia, limited empirical evidence exists regarding the implementation of HRM practices in secondary schools, especially in relation to teacher induction, performance appraisal, and motivation. This study investigates the prevailing HRM practices and the institutional challenges affecting their implementation in Ethiopian secondary schools. A concurrent mixed-methods research design was employed to obtain both quantitative and qualitative insights. Quantitative data were collected from 262 secondary school teachers through structured questionnaires, while qualitative data were obtained from 12 purposively selected school leaders and administrative personnel through semi-structured interviews. The quantitative data were analyzed using one-sample t-tests and multivariate analysis of variance (MANOVA), whereas qualitative findings were analyzed thematically to support data triangulation. The findings reveal that the implementation of major HRM functions remains below the expected standard across the sampled schools. Teacher induction programs were inadequately structured, performance appraisal systems lacked developmental orientation and constructive feedback mechanisms, and motivational practices were constrained by insufficient financial and non-financial incentives. The study further identified several institutional barriers, including limited leadership capacity, inadequate supervision, low salary structures, weak professional recognition systems, and insufficient opportunities for professional development. Moreover, MANOVA results indicate that demographic variables such as gender, educational status, work experience, and school context did not significantly influence teachers’ perceptions of HRM practices. This study contributes to the growing discourse on context-specific HRM in developing educational systems by demonstrating how structural and managerial constraints hinder effective human resource management in public secondary schools. The findings highlight the need for adaptive HRM policies, school-based performance management frameworks, and sustainable teacher motivation strategies to strengthen educational quality and institutional effectiveness in Ethiopia.